Global stability of a double-delay HIV dynamical model with curative mechanism, absorption effect, and Beddington–DeAngelis functional response - Silva, P. Damith Nilanga; Guo, Songbai; Aruna Pradeep, B.G. Sampath (Nonlinear Analysis: Modelling and Control, 2026)
This study examines the stability of a modified mathematical model for HIV infection, including two time delays. The novel aspect is that both the absorption effect and the cure rate are incorporated into the model with the Beddington–DeAngelis (BD) functional response. The global asymptotic stability of the infection-free equilibrium and uniform persistence of the model are established. To corroborate the theoretical outcomes, the numerical simulations are illustrated. Numerical simulations reveal how the two time delays, cure rate, and BD functional response influence the eradication of the disease.